'Value flows' between talent and their networks: a case study of international graduates working in Vietnam's emerging economy. Issue 11 (17th June 2022) - Pham, Lien; Dang, Quyen Thao
Abstract: This paper explores issues relating to talent management in Vietnam's emerging market economy, particularly knowledge transfer, skills application, and linkage effects within and across firms. The paper offers the concept of 'value' to consider employees' knowledge, skills, and attributes, and 'value flows' as the deployment of these resources. This value-based approach to talent management is illustrated using qualitative data collected from semi-structured interviews with Vietnamese international graduates' and members of their employment networks. The focus on international graduates considers the Vietnamese government's policies of internationalisation of higher education as a strategic investment to improve the quality of human resources to meet the country's socioeconomic development needs for global integration. The paper offers some implications for policies and practices to develop and harness talent in emerging economies like Vietnam.